Opioid use disorder in Germany: healthcare costs of patients in opioid maintenance treatment - Reimer, Jens (Subst Abuse Treat Prev Policy, 2019)
BACKGROUND: Opioid Use Disorder (OUD) is a substance use disorder with a chronic course associated with comorbid mental and somatic disorders, a high burden of psychosocial problems and opioid maintenance treatment (OMT) as a standard treatment. In the US, OUD imposes a significant economic burden on society, with annual societal costs estimated at over 55 billion dollars. Surprisingly, in Europe and especially in Germany, there is currently no detailed information on the healthcare costs of patients with OUD. The goal of the present research is to gather cost information about OUD patients in OMT with a focus on maintenance medication and relapses. METHODS: We analysed health claims data of four million persons covered by statutory health insurance in Germany, applying a cost-of-illness approach and aimed at examining the direct costs of OMT patients in Germany. Patients with an ICD-10 code F11.2 and at least one claim of an OMT medication were stratified into the treatment groups buprenorphine, methadone or levomethadone, based on the first prescription in each of the follow-up years. Costs were stratified for years with and without relapses. Group comparisons were performed with ANOVA. RESULTS: We analysed 3165 patient years, the total annual sickness funds costs were on average 7470 € per year and patient. Comparing costs of levomethadone (8400 €, SD: 11,080 €), methadone (7090 €, SD: 10,900 €) and buprenorphine (6670 €, SD: 7430 €) revealed significant lower costs of buprenorphine compared to levomethadone (p < 0.0001). In years with relapses, costs were higher than in years without relapses (8178 € vs 7409 €; SD: 11,622, resp. 10,378 €). In years with relapses, hospital costs were the major cost driver. CONCLUSIONS: The present study shows the costs of OUD patients in OMT for the first time with a German dataset. Healthcare costs for patients with an OUD in OMT are associated with more than two times the cost of an average German patients. Preventing relapses might have significant impact on costs. Patients in different OMT were dissimilar which may have affected the cost differences.